2002
DOI: 10.1063/1.1487920
|View full text |Cite
|
Sign up to set email alerts
|

Controlled alignment of carbon nanofibers in a large-scale synthesis process

Abstract: Controlled alignment of catalytically grown carbon nanofibers ͑CNFs͒ at a variable angle to the substrate during a plasma-enhanced chemical vapor deposition process is achieved. The CNF alignment is controlled by the direction of the electric field lines during the synthesis process. Off normal CNF orientations are achieved by positioning the sample in the vicinity of geometrical features of the sample holder, where bending of the electric field lines occurs. The controlled growth of kinked CNFs that consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 17 publications
4
84
1
Order By: Relevance
“…Merkulov et al demonstrated that the CNTs grown at the vicinity of the substrate holder, where the electric field is curved, also exhibited corresponding curved shapes. [48] The ability of guiding the growth direction of CNTs by electric field enables large freedom in manipulating CNT morphologies by external bias. In this case, the growth direction of the CNT arrays is primarily controlled by the external electric field.…”
Section: Electrically Guided Alignment Of Carbon Nanotubesmentioning
confidence: 99%
“…Merkulov et al demonstrated that the CNTs grown at the vicinity of the substrate holder, where the electric field is curved, also exhibited corresponding curved shapes. [48] The ability of guiding the growth direction of CNTs by electric field enables large freedom in manipulating CNT morphologies by external bias. In this case, the growth direction of the CNT arrays is primarily controlled by the external electric field.…”
Section: Electrically Guided Alignment Of Carbon Nanotubesmentioning
confidence: 99%
“…CNF can be produced by traditional vapor growth method [6] or plasma enhanced chemical vapor depositing method [7]. However, vapor growth or plasma enhanced chemical vapor depositing method involved a complicated process and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CNFs the electric field of a plasma environment controls the growth directionality 13 , whereas it is the interaction between CNTs grown at a high enough density and rate which induces the vertical alignment in the forest configuration 14 . The CNFs have a complex internal structure with less order than a nanotube 9 , but one advantage is that individual vertically aligned nanostructures can be grown.…”
Section: Device Fabrication and Characterizationmentioning
confidence: 99%